Ethnobotanical documentation of medicinal flora traditionally used for pediatric diseases in Khar, district Bajaur, Khyber Pakhtunkhwa, Pakistan - Shariat, Ullah; Wahid Hussain; Sahar Nasim; Sajjad Ahmad; Sulaiman Khan; Shah Faisal; Amjid Ali (Ethnobotany Research and Applications, 2025)
Background: The use of plants for primary healthcare continues in both developed and developing countries. In rural areas, where healthcare facilities are limited, conventional medicine is expensive, and resources are often mismanaged, parents turn to herbal remedies instead of modern medicine to treat children’s illnesses. Therefore, it is crucial to document the ethnomedicinal use of plants for children’s healthcare in the studied regions. Objectives: The aim of this study was to document ethnomedicinal plants used for treating children’s disorders and assess their conservation status. Methods: The data was collected using a semi-structured questionnaire, incorporating various quantitative indices such as Relative Frequency of Citation (RFC) and Family Importance Value (FIV). Plant specimens identified by local informants were collected and verified with the aid of existing literature. The accuracy of scientific names was confirmed through the International Plant Names Index (IPNI) database. (IPNI) https://www.inpni.org. Results: A total of forty six different medicinally important plants belonging to twenty eight families were recorded utilizing for the curing of children disorders during March to December 2023. The Lamiaceae family, with six species, was reported to have the highest number of plants used for treating children’s illnesses, followed by five species from other families. Seeds (30%) and leaves (28%) were the most commonly used plant parts by the local inhabitants. According to the family importance value, Apiaceae ranked highest (82.92%), followed by Lamiaceae (80.48%), while the species Ammi visnaga had the highest relative frequency of citation (0.48). The conservation status indicated that 47.82% of the plants were considered rare, while 41.3% were classified as vulnerable. The highest informant consensus was observed for abdominal pain (15 species), followed by diarrhea (6 species), and constipation, wounds, and chest infections (5 species each). Conclusion: This study documents ethnomedicinal plants from various areas of Khar, District Bajaur, focusing on those used for paediatric diseases. It does not target a specific disease or involve quantitative analysis. There are significant gaps in ethnobotanical knowledge in this region of Khyber Pakhtunkhwa, Pakistan, with much of the knowledge held by traditional societies at risk due to lack of documentation. Many medicinal plants are also facing extinction, threatening genetic diversity. The study aims to preserve this knowledge to support the development of affordable, low-cost therapies for the poor. Keywords: Quantitative, Ethnobotany, Conservation, diseases, Bajaur, Pakistan.